Education System Reform in Pakistan: Why, When, and How? - Mehnaz Aziz; David E. Bloom; Salal Humair; Emmanuel Jimenez; Larry Rosenberg; Zeba Sathar (Institute for the Study of Labor (IZA), 2014)
Pakistan's education system faces long-standing problems in access, quality, and equal opportunity at every level: primary and secondary schools, higher education and vocational education. In spite of recent encouraging trends, such as the rapid spread of private schooling and an expansion of higher education opportunities, systemic reform remains stubbornly elusive. The inability of successive governments to reform the system has created severe constraints for Pakistan's economic and societal development. An inability to act now will increase the problems manifold in the future, due to a burgeoning youth population and increasing competitive pressures from other developing countries that are devoting more attention to education. We discuss in this paper the imperative for education system reform in Pakistan, and articulate why a window of opportunity exists at this time for all stakeholders government, civil society and donors to initiate reform. We emphasize, however, some key messages. One, that reform must tackle all sectors of the education system primary/secondary, higher education and vocational education as Pakistan does not have the luxury to delay reform in one sector until the other sectors improve. Two, reform in every sector must be systemic i.e. with well-defined goals, focus on a minimal set of areas such as governance, financing, human resources, and curriculum and address them all together, rather than piecemeal. Three, implementation is the all-important Achilles' heel, where Pakistan has limited resources and has often foundered on the rocks. But as we discuss, there are important examples demonstrating that success is achievable, if government and civil society have the will to initiate and sustain reform.
Keywords: I21; I25; I28; H52; 330; education; economic development; educational reform; Pakistan